Analisis Dimensi Fraud Diamond Dan Gone Theory Terhadap Academic Fraud (Studi Kasus Mahasiswa Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta) - Pratama, Reza Yuka Satria; , Dr. Noer Sasongko, S.E., M.Si., AK., CA (2017)
This study aimed to analyze the influence of Diamond Fraud and GONE Theory in academic cheating behavior done by the students. Diamond Fraud Based on the theory there are four variables that affect academic cheating is suspected, namely pressure, opportunity, rationalization and capabilities. Meanwhile, Gone Based Theory there are three variables that affect academic cheating is Greed, Need and Exposures The population of this research is the students of the faculty of economics and business Muhammadiyah University of Surakarta. In this study, the hypothesis was tested using multiple regression. The results showed that opportunity, rationalization and capabilities to influence the behavior of a student's academic cheating. Meanwhile, pressure, greed, need and exposures do not affect the students' academic cheating behavior. Keywords: Academic Fraud, Fraud Diamond, GONE Theory